Sepsis Patients with First and Second-Hit Infections Show Different Outcomes Depending on the Causative Organism - Morgan, Matt P.; Szakmany, Tamas; Power, Sarah G.; Olaniyi, Patrick; Hall, Judith E.; Rowan, Kathy; Eberl, Matthias (Frontiers in Microbiology, 2016)
Objective. With improving rates of initial survival in severe sepsis, second-hit infections that occur following resolution of the primary insult carry an increasing burden of morbidity. However, despite the clinical relevance of these infections, no data are available on differential outcomes in patients with first and second-hit infections depending on the nature of the causative organism. This study aims to explore any differences in these subgroups. Design. In a retrospective, observational cohort study, the United Kingdom Intensive Care National Audit and Research Centre (ICNARC) database was used to explore the outcomes of patient with first-hit infections leading to sepsis, and sepsis patients with second-hit infections grouped according to the Gram status of the causative organism. Setting. General critical care units in England, Wales, and Northern Ireland participating in the ICNARC programme between 1 January 2007 – 30 June 2012. Patients. Patient groups analysed included 2119 patients with and 1319 patients without sepsis who developed an intensive care unit acquired infection in blood. Subgroups included patients with trauma, emergency neurosurgical, elective surgical, and cardiogenic shock. Measurements and main results. Gram-negative organisms were associated with poorer outcomes in first-hit infections. The 90-day mortality of patients who developed a Gram-negative infection was 43.6% following elective surgery and 27.9% following trauma. This compared with a mortality of 25.6% and 20.6%, respectively, in Gram-positive infections. Unexpectedly, an inverse relationship between Gram status and mortality was observed in second-hit infections. Patients with an initial diagnosis of sepsis who developed secondary infections caused by Gram-negative organisms had a 90-day mortality of 40.4%, compared with 43.6% in Gram-positive infections. Conclusions. Our study identifies a fundamental difference in patient outcomes between first-hit and second-hit bacterial infections, which may be due to genetic, microbiological, immunological, and environmental factors. This finding has direct implications for risk stratification and defines future research priorities.